The influence of anger on empathy and theory of mind. - Ronja Weiblen (Public Library of Science (PLoS), 2021)
Social cognition allows humans to understand and predict other people's behavior by inferring or sharing their emotions, intentions and beliefs. Few studies have investigated the impact of one's own emotional state on understanding others. Here, we tested the effect of being in an angry state on empathy and theory of mind (ToM). In a between-groups design we manipulated anger status with different paradigms in three studies (autobiographical recall (N = 45), negative feedback (N = 49), frustration (N = 46)) and checked how this manipulation affected empathic accuracy and performance in the EmpaToM. All paradigms were successful in inducing mild anger. We did not find the expected effect of anger on empathy or ToM performance but observed small behavioral changes. Together, our results validate the use of three different anger induction paradigms and speak for rather weak behavioral effects of mild state anger on empathy and ToM.